Penyuluhan Formulasi Spray Anti Nyamuk dari Infusa Limbah Daun Serai (Cymbopogon nardus) dan Kulit Buah Jeruk Nipis (Citrus aurantifolia) - Damaranie Dipahayu; Siti Annurijati (Jurnal Abdi Masyarakat Kita, 2022)
Dengue fever is endemic in Indonesia. Using mosquito repellent is an effective way to prevent mosquito bites. This community service is in the form of webinar “the formulation of an anti-mosquito spray used infusion method of lemongrass (Cymbopogon nardus) leaf and lime peel (Citrus aurantifolia)”. Natural formula is safer than chemicals especially for children. The audiences of this counseling are the parents and teachers of KB-RA Perwanida's. Counseling accompanied by video playback of formulations and question and answer discussions. The mosquito repellent spray had an attractive color, fresh aroma and moisture on the skin. The audiences stated that the webinar was very useful so that it was usefull and meet the target